PENGADILAN HAK ASASI MANUSIA DAN MAHKAMAH PIDANA INTERNASIONAL (ICC) - Zulkarnain, Zulkarnain (AKTUALITA, 2011)
of exhaustion of local remedies through the mechanism of a national judicial forum.Mechanisms in resolving the violations of human rights at the national level are usuallyformed by a country by establishing a special court of human rights. Indonesian HumanRights Court established in the year of 2000 as a step up from the Article 104 of Law No.39 Year of 1999 about the Human Rights. Jurisdiction of that Human Rights courtincludes serious violations of human rights as the crimes against Genocide and humanity.Furthermore, the mechanism in resolving the violation of human rights at theinternational level consists of the Human Rights court that is ad hoc and permanent.International Criminal Court (ICC) is a first permanent international criminal courtwhich has authorities to investigate, prosecute and punish all people who commit themost serious international crimes, such as genocide, crimes against humanity, war andaggression crimes.Keywords: gross violation of human rights, Rome Statute of 1998, the internationalcriminal court, the court of human rights in Indonesia.